Konsep Amwal dalam Al-Qur'an dan Hadits - Surono, Yudi; Gunawan, Aan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The concept of amwal in the Qur'an and Hadith is an important topic in Islamic economic studies, which is related to the understanding of wealth, ownership, and management. Amwal, which means